Cryopreservation Effect on Proliferative and Chondrogenic Potential of Human Chondrocytes Isolated from Superficial and Deep Cartilage - Muiños-López, Emma (Bentham Open, 2012)
OBJECTIVES: To compare the proliferative and chondrogenic potential of fresh and frozen chondrocytes isolated from superficial and deep articular cartilage biopsies. MATERIALS AND METHODOLOGY: The study included 12 samples of fresh and frozen healthy human knee articular cartilage. Cell proliferation was tested at 3, 6 and 9 days. Studies of mRNA quantification, protein expression and immunofluorescence for proliferation and chondrogenic markers were performed. RESULTS: Stimulation of fresh and frozen chondrocytes from both superficial and deep cartilage with fetal bovine serum produced an increase in the proliferative capacity compared to the non-stimulated control group. In the stimulated fresh cells group, the proliferative capacity of cells from the deep biopsy was greater than that from cells from the superficial biopsy (0.046 vs 0.028, respectively, p<0.05). There was also a significant difference between the proliferative capacity of superficial zone fresh (0.028) and frozen (0.051) chondrocytes (p<0.05). CCND1 mRNA and protein expression levels, and immunopositivity for Ki67 revealed a higher proliferative capacity for fresh articular chondrocytes from deep cartilage. Regarding the chondrogenic potential, stimulated fresh cells showed higher SOX9 and Col II expression in chondrocytes from deep than from superficial zone (p<0.05, T student test). CONCLUSIONS: The highest rate of cell proliferation and chondrogenic potential of fresh chondrocytes was found in cells obtained from deep cartilage biopsies, whereas there were no statistically significant differences in proliferative and chondrogenic capacity between biopsy origins with frozen chondrocytes. These results indicate that both origin and cryopreservation affect the proliferative and chondrogenic potential of chondrocytes.